Buy or make? Agricultural production diversity, markets and dietary diversity in Afghanistan. (August 2019) - Zanello, Giacomo; Shankar, Bhavani; Poole, Nigel
Highlights: We examine the interplay of production diversity, markets and dietary diversity. We use a nationally representative household data from Afghanistan. Greater cropping diversity improves dietary diversity in the regular season. Improved market food availability boosts dietary diversity in the lean season. Improved livestock diversity has a positive influence on diets throughout the year. Abstract: Increasing on-farm production diversity and improving markets are recognized as ways to improve the dietary diversity of smallholders. Using instrumental variable methods to account for endogeneity, we study the interplay of production diversity, markets and diets in the context of seasonality in Afghanistan. We confirm an important seasonal dimension to the interplay. Improved crop diversity over the year is positively associated with dietary diversity in the regular season, but not in the lean season. Livestock species diversity remains important for dietary diversity throughout the year, but particularly so in the lean season when the influence of cropping diversity is low. Market aspects become important for dietary diversity specifically in the lean season.